PELATIHAN MANAJEMEN USAHA BUDIDAYA KOPI SEBAGAI UPAYA PERBAIKAN TEKNIK BUDIDAYA DAN PENINGKATAN PEMAHAMAN PENCATATAN KEUANGAN USAHA - Apri Andani; Redy Badrudin; M. Mustopa Romdhon (DHARMA RAFLESIA, 2018)
This activitiy has purposes to give a training about farming management, especially technical aspect and financial recording for coffee farming business. The target of this program is coffee farmers. The location is taken place in Baru Manis Village, Bermani Ulu Subdistrict, Rejang Lebong District, Bengkulu Province. The method used in this activity is extension approach method and combination with small group discussion and practice. The result show that farmers face many problem about their farming system. Their coffee has been attacted by some diseases that they never known before. After taken this activity they know that their plant are not always being attacted by pest, but some signs show that it is fungi or root disease. Furthermore, in financial aspect, they never take notes about how much money they have spent for their farming because they do not know how to write it in a good way. After taking this program, they learn how to record cost, price, and their return from their coffee. It can be said that this activity is needed and success. Keywords: farming management, technical skill, financial record, coffee